2022
DOI: 10.1080/02687038.2022.2159314
|View full text |Cite
|
Sign up to set email alerts
|

Structural priming from production to comprehension in aphasia

Abstract: Background: Many persons with aphasia (PWA) show deficits in sentence production and comprehension which are, in part, attributed to an inefficient mapping between messages and syntactic structures. Structural priming-the tendency to repeat a previously encountered sentence structure-has been shown to support implicit syntactic learning within and across production and comprehension modalities in healthy adults. Structural priming is effective in facilitating the production or comprehension of sentences in PWA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Additionally, the current findings suggest that the alignment process of message-sentence structure mappings in an interactive language task remains preserved in aphasia, extending the burgeoning evidence of the positive effects of structural priming in PWA (for production: Saffran and Martin, 1997;Hartsuiker and Kolk, 1998;Cho-Reyes et al, 2016;Yan et al, 2018;Lee et al, 2019;Man et al, 2019;van Boxtel et al, 2023;for comprehension: Lee et al, 2019;Keen and Lee, 2022). Implicit structural priming is effective in facilitating sentence processing in PWA across different linguistic representations (syntactic, lexical), task types (monologue, dialogue), and delivery modes (in-person, TelePriming).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, the current findings suggest that the alignment process of message-sentence structure mappings in an interactive language task remains preserved in aphasia, extending the burgeoning evidence of the positive effects of structural priming in PWA (for production: Saffran and Martin, 1997;Hartsuiker and Kolk, 1998;Cho-Reyes et al, 2016;Yan et al, 2018;Lee et al, 2019;Man et al, 2019;van Boxtel et al, 2023;for comprehension: Lee et al, 2019;Keen and Lee, 2022). Implicit structural priming is effective in facilitating sentence processing in PWA across different linguistic representations (syntactic, lexical), task types (monologue, dialogue), and delivery modes (in-person, TelePriming).…”
Section: Discussionsupporting
confidence: 74%
“…After hearing or repeating prime sentences, PWA are able to produce sentences that they could not produce otherwise more frequently (Saffran and Martin, 1997;Hartsuiker and Kolk, 1998;Yan et al, 2018), and these priming effects persist over intervening filler utterances (Cho-Reyes et al, 2016;Lee et al, 2019;Man et al, 2019). Priming experience in the production modality shapes the ways in which PWA interpret subsequent syntactically ambiguous sentences, suggesting that structural priming creates enduring changes in the central syntactic system (Keen and Lee, 2022). In a recent eyetracking structural priming study, van Boxtel and colleagues found that a group of PWA showed cumulative improvement in the production accuracy of passive sentences and the use of an advanced sentence planning strategy, even when they failed to show significant immediate priming effects (van Boxtel et al, 2023).…”
Section: Introductionmentioning
confidence: 99%